Aporte de nutrientes na sub-bacia do ribeirão Bom Jardim (Triângulo Mineiro) e proposição de diretrizes para programas de Pagamento por Serviços Ambientais - Santos, Alessandra Campos dos (2018)
Pollution and degradation of water resources, mainly by anthropic activities, is one of the major challenges of water management. The advancement of agriculture and livestock in natural vegetation areas can compromise the supply of water in quantity and quality, since these activities usually require the use of fertilizers and pesticides. The main objective of this work is to simulate the loads of ammoniacal nitrogen, nitrate, nitrite and phosphorus that are carried in the sub-basin of the Bom Jardim river, for different scenarios of land use, and also propose conservation guidelines for the implementation of Environmental Services Payment (PES) programs. This sub-basin is located between Uberlândia and Uberaba (Triângulo Mineiro, MG), and its watercourses feed the Bom Jardim water reservoir, destined for the public supply of the city of Uberlândia. The hydrological and nutrient simulations were performed using the Soil and Water Assessment Tool (SWAT), and compared with values obtained through field analysis. In addition, the abatement indices of these nutrients were calculated for different scenarios of land use. Finally, the guidelines for the implementation of PES programs were proposed from a literature review of articles, theses, dissertations, manuals and books about the subject. The results generated by the SWAT simulations showed, in general, that the areas occupied by agriculture tend to generate a greater amount of nutrients, which are later carried to the watercourses, mainly through surface runoff. The simulations also showed that the substitution of areas of agriculture for forest reduces the generation and the contribution of nutrients in the sub-basin of the Bom Jardim river. The nitrate and phosphorus discharges measured in the field were close to the values simulated by the SWAT, on the other hand, the discharges of nitrite and ammoniacal nitrogen were much higher than those simulated. About the nutrient abatement rates, nitrate was shown to be the most sensitive to modifications, indicating that a given substitution by forest can compensate in a greater attenuation of this nutrient. The proposed guidelines for the implementation of PES programs in the sub-basin of the Bom Jardim river were: definition of the environmental service; definition of the providers and the areas where the program will be implemented; actions so that the provision of this service is guaranteed; forms of financing; average transaction value for preserved environmental service; agreement between the parties; monitoring and inspection system. Because it was a pioneer study in a sub-basin with no data, it was not possible to perform the calibration and validation of the results obtained by the SWAT model simulations. In addition, the small number of campaigns (three) does not allow a complete characterization of the studied region, thus, it is recommended to continue the water analysis and flow measurement at the sampling points, in order to construct a curve for the discharge of nutrients.